Avaliação do estado nutricional e prevalencia de anemia de crianças de creches da regional leste de Belo Horizonte, MG - Daniela da Silva Rocha (2006)
The present study investigated anemia prevalence, nutritional status and nutritional deficit risk factors in infants and children enrolled in daycare facilities. Four hundred and two infants and children aged 7 to 74 months, enrolled in 25 public daycare facilities in the eastern regional district of the city of Belo Horizonte, were evaluated. Capillary blood was used to measure hemoglobin (Hb) using disposable microcurvettes and evaluated with a portable hemoglobinmeter (HemoCue). Infants and children were considered anemic with hemoglobin levels less than 11.0 g/dL for age group 6 to 59 months, and hemoglobin levels less than 11.5 g/dL in children aged 60 to 74 months of age. Anemia was defined using the following classification: severe anemia (Hb < 7.0 g/dL); moderate anemia (Hb between 7.0 and 9.0 g/dL) and brand anemia (Hb > 9.0g/dL and < 11.0 g/dL). Anthropometric data on weight and height were measured and expressed as Z-score using anthropometry indexes for weight-for-age, height-for-age and weight-for-height and classified according to three groups: < -2 (malnutrition), < -2 to values < -1 (nutritional risk for malnutrition) and -1. To exam factors of nutritionaldeficiency, Z-score values less than -1 were used. Enrollment time in daycare was calculated as the difference between baseline evaluation and the enrollment dates of infant and children. Anemia prevalence and nutritional status were evaluated in 402 infants and children with mean age of 45.4 ± 16.2 months. Overall anemia prevalence was 28.8%. When divided into age groups, 80%, 70.3%, 32%, 21.8%, 21.3% and 22.2%of infants and children pertaining to age groups less than 12, 12 to 24, 24 to 36, 36 to 48, 48 to 60 and 60 to 73.5 months, respectively, were diagnosed with anemia. Mean hemoglobin increased with age, however, infants and children aged less than 24 months had below cut-off values for anemia. The prevalence of malnutrition (<-2 Z-score) was 5% and 5.5% for weight-for-height and weight-for-age, respectively. The prevalence of stunting was 4.2%. There was a significant between anemia and age and a deficiency in height (p<0.05). A sub-sample of 312 infants and children were evaluated to determine risk factors for nutritional deficits, of which 51.9% were boys, and a greater part of the subjects were greater than 48 (56.4%) months of age; 30.1% were between 24 and 48, and 13.5% had less than or equal to 24 months of age. The prevalence of malnutrition, according to weight-for-age and weight-for-height Z-score index was 5.1% and 4.5%, respectively. Stunting was seen in 3.8% of the subjects. Nutritional risk in infants andchildren was shown more frequent in height-for-age (18.3%), followed by weight-forage (16.3%) and weight-for-height (12.2%). Variables statistically significant in relation to nutritional deficits were as followed: low birth weight, paternal education ( elementary school education) and low income earnings (< R$ 135.50 reais). Infants and children enrolled in daycare facilities in the eastern region of Belo Horizonte were considered moderately anemic, most of which had less than 24 months of age. Although there were a predominancy of the acute nutritional deficiency, it has to point out the higher risk for the chronic malnutrition (height/age).